2022
DOI: 10.1002/pon.5980
|View full text |Cite
|
Sign up to set email alerts
|

Cancer‐related cognitive impairment in survivors of adolescent and young adult non‐central nervous system cancer: A scoping review

Abstract: Objectives Cancer‐related cognitive impairments (CRCI) are common after treatment and can have important impacts on the lives of adolescent and young adult (AYA) cancer survivors—those cancer survivors diagnosed between ages 15 and 39. However, most research focuses on survivors diagnosed under age 15 or over age 39 so we know relatively little about CRCI among AYA survivors of non‐central nervous system (CNS) cancers. Here we review the research on CRCI among AYA survivors of non‐CNS cancers to determine prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 55 publications
(231 reference statements)
2
6
0
Order By: Relevance
“…The participants experienced challenges in daily life with impaired physical and cognitive functioning during oncological treatment, consistent with previous studies (71,116). Despite struggling with impairments, participants were resourceful and described that they were able to maintain meaningful daily activities and participate in social life but had to make adjustments according to their capacity.…”
Section: Experiences Of Functioning In Daily Lifesupporting
confidence: 82%
“…The participants experienced challenges in daily life with impaired physical and cognitive functioning during oncological treatment, consistent with previous studies (71,116). Despite struggling with impairments, participants were resourceful and described that they were able to maintain meaningful daily activities and participate in social life but had to make adjustments according to their capacity.…”
Section: Experiences Of Functioning In Daily Lifesupporting
confidence: 82%
“…The most recent review by Vizer et al (2022) includes studies about the cognitive impairment faced by people under 39 years of age with cancer located outside the central nervous system (CNS). The review found that CRCI affects approximately 26% of subjects of this age [ 23 ]. For all of the reasons cited above, patient age was not an inclusion criterion for our own study.…”
Section: Discussionmentioning
confidence: 99%
“…Vizer et al (2022), in their systematic review, highlight that of the 21 articles included in the review, only one was a study using an intervention, even though various types of activities can improve cognitive function. Interventions using digital methods, which can be a practical and effective option, were also not addressed [ 23 ]. The need for cognitive rehabilitation was noted by Dos Santos et al [ 11 ], who demonstrated that training using computer-based methods led by a neuropsychologist is more effective than mental tasks performed at home or no mental exercises.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, this review article may be as specific as possible to the assessment of chemotherapy-induced cognitive dysfunction. The scoping review by Vizer et al (2022) should be referenced since it focused on studies on the Adolescent and Young Adult (AYA) generation, which was not the focus of the present review.…”
Section: Discussionmentioning
confidence: 99%